Advanced PHP programming : a practical guide to developing large-scale Web sites and applications with PHP 5 - Schlossnagle, George (Developer's library., 2004)
Over the past three years PHP has evolved from being a niche language used to add dynamic functionality to small sites to a powerful tool making strong inroads into large-scale, business-critical Web systems. The rapid maturation of PHP has created a skeptical population of users from more traditional "enterprise" languages who question the readiness and ability of PHP to scale, as well as a large population of PHP developers without formal computer science backgrounds who have learned through the hands-on experimentation while developing small and midsize applications in PHP. While there are many books on learning PHP and developing small applications with it, there is a serious lack of information on "scaling" PHP for large-scale, business-critical systems. Schlossnagle's Advanced PHP Programming fills that void, demonstrating that PHP is ready for enterprise Web applications by showing the reader how to develop PHP-based applications for maximum performance, stability, and extensibility.